Pengembangan Model Climate Smart School Berbasis Ketangguhan Sekolah (School Resilience) untuk Memperkuat Kapasitas Adaptasi terhadap Perubahan Iklim dan Risiko Bencana - Lalu Muhammad Alfian; Moh. Taqiuddin; M.A.Muazar Habibi (Universitas Mataram, 2026)
Schools in disaster-prone areas require an integrated approach to address climate change and geophysical hazards. This study aimed to develop, validate, and assess the initial effectiveness of the Adaptive Climate Smart School–School Resilience model (CSS-SR) in strengthening the school community's adaptive capacity. A Research and Development design was applied using a modified ADDIE procedure and a sequential exploratory mixed-methods strategy. The needs assessment involved eight informants, while the effectiveness test included 60 school members, comprising 42 students and 18 teachers/staff, together with expert and practitioner validators. Findings revealed the absence of a formal climate program, unsystematic adaptive-capacity practices, and outdated preparedness facilities, despite strong school social capital. The developed context-sensitive model comprised five dimensions and eleven operational components. It was rated highly valid by the content expert (86.67%) and media experts (88.33%), and highly practical by practitioners (87.78%) and users (85.56%). Wilcoxon tests indicated significant short-term improvements across all instruments (p<0.001; r=0.749–0.870). The model demonstrated initial effectiveness; however, the findings should be interpreted cautiously because of ceiling effects and the absence of a comparison group.